2019
DOI: 10.1002/er.4394
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of novel heat pump cycles for drying process with large temperature lift

Abstract: Summary Heat pump–assisted drying has been recognized a prospective technology to meet the requirement of energy saving. However, large temperature lift will be resulted by the single‐stage heat pump cycle during the high‐temperature drying, especially operating with low ambient temperature for open‐loop drying, which leads to insufficient heat output, high compression ratio, and low coefficient of performance (COP). Two heat pump cycles, namely, multitemperature cascade cycle and combined single‐stage cycle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The SAHP drying system is preferred for chili peppers because the rates of heat and mass transfer are high and it is capable of working throughout nighttime and daytime . A couple of heat pump cycles, multitemperature cascade cycle and combined single‐stage cycle, has been recommended to tackle the aforementioned shortcomings in drying process with large temperature lift . The impact of various operation variables on heat pump cycles has been studied to develop an optimal cycle performance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SAHP drying system is preferred for chili peppers because the rates of heat and mass transfer are high and it is capable of working throughout nighttime and daytime . A couple of heat pump cycles, multitemperature cascade cycle and combined single‐stage cycle, has been recommended to tackle the aforementioned shortcomings in drying process with large temperature lift . The impact of various operation variables on heat pump cycles has been studied to develop an optimal cycle performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the bi‐cascade cycles (ie, traditional cascade cycle and multitemperature cascade cycle), 49% more water evaporation with identical power may be produced through adding condenser and evaporator. Among the five cycles being examined, the multitemperature cascade cycle was found to be the optimal for retrofitting the drying equipment with large temperature lift …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The productivity of the suggested plant was compared, where the results indicated that by raising the CO 2 discharging pressure the system could operate more effectively, as the COP and exergy efficiencies were enhanced by 54.7% and 17.5%, respectively. In another research, two innovative heat pump systems were designed and analyzed for drying purposes by Peng et al 19 The heat pumps were, in fact, poly‐temperature cascade and integrated single‐stage heat pumps. The authors also optimized their systems by examining and comparing the impacts of varying operation parameters.…”
Section: Introductionmentioning
confidence: 99%